Index of the cycle of money: The case of Greece - Constantinos Challoumis (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: The purpose of this paper is to apply the theory of cycle of money in the case of Greece. Prior works have determined the economic characteristics of the case of Latvia, Serbia, and Bulgaria, according to the concept of the theory of cycle of money. The index of the cycle of money suggests how an economic system should counteract a monetary and fiscal crisis and studies how well-structured is Greece's economy. The estimations of the index of the cycle of money of Greece are compared with the global average index of the cycle of money. The results reveal that Greece is above the average global value. Then, Greece's results reveal that it is a well-structured economy and can face an economic crisis. The current work is important as represents the strength of Greece's economy with emphasis to the period of 2012 - 2017, of financial and economic crisis. The theory of the cycle of money covers the gap that exists for the structure and functionality of the economy, which formed on the derivative of GDP, giving the cycle of money. Moreover, it is the only theory that enhances the economy, without any negative effect of the fiscal or the monetary policy, as uses the same amount of money of an economy appropriately. Design/methodology/approach: The applied methodology stands on the analysis of the theory, mathematical, statistical, and econometrical results. Findings: The study found that the general index of the cycle of money for the case of Greece is 0.72, showing that the distribution of money is at the upper level, revealing the very good strength of the Greek economy, with a very well-based economic structure and high economic functionality, meaning high distribution and reuse of money. Research limitations/implications: This work is from a project for multiple countries. Concluding, the recent decision of 15% minimum tax to the international companies complies with the Fixed Length Principle of the theory of cycle of money that developed the last years. Originality/value: This study contributes to the theory of the cycle of money and shows that Greece belongs to the countries which have top rates to the distribution of money, explaining why Greece against to huge financial crisis of the prior decade, achieved to recovered.
Keywords: F6; F40; F43; F62; F63; 330; Index of the cycle of money; Greece; the cycle of money